Ultraviolet-visible study of tautomeric behavior of some carbonyl and thiocarbonyl pyrimidine derivatives: Experimental evidence of enolization and thioketonization - KILIÇ, HASAN (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Tautomeric behaviors of the protonated forms of recently synthesized 1-Amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one (I), and 1-Amino5-benzoyl-4-phenyl-1H-pyrimidine-2-thione (II), were investigated with respect to pH and time in aqueous methanol (5%, v/v methanol) and in pure methanol by electronic absorption spectra to elucidate the nature of the tautomeric interconversions and the role of carbonyl oxygen in I and thiocarboryl sulfur in II. At room conditions, the carbonyl group at position 2 in I was found to undergo a significant spontaneous enolization (66%) at pH 1.0 in aqueous methanol medium in 8 h. On the other hand, thioketonization for the protonated form of the thiocarbonyl group in 11 was comparably small (37%) in pure methanol at pH 10.0 over a 5-day period. The interconversion mechanism was identified for each compound using the UV-vis data. The equilibrium constant for each compound was estimated in an ionic strength of 0.10 M (LiCl) at room temperature, from the ratios of molar absorptivities of the pure tautomeric forms. For I, the spontaneous enolization equilibrium constant (pK(enol)) was 0.291 in aqueous methanol solution, while the thioketonization equilibrium constant (PKthiocarhonyl) for II was 0.234 in pure methanol. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: enolization; thioketonization; carbonyl; thiocarbonyl; carbonyl-enol; thiocarbonyl-thioenol; heterocyclic compounds; pyrimidine derivatives; UV spectrometry; ACID-BASE EQUILIBRIA; SPECTRAL INVESTIGATIONS; OXALYL COMPOUNDS; ENOL; KETO